Transcription regulators and hormones involved in the development of brown fat and white fat browning: transcriptional and hormonal control of brown/beige fat development - Zhang, J; Wu, H; Ma, S; Jing, F; Yu, C; Gao, L; Zhao, J (Physiological research, 2018)
The high prevalence of obesity and related metabolic complications has inspired research on adipose tissues. Three kinds of adipose tissues are identified in mammals: brown adipose tissue (BAT), beige or brite adipose tissue and white adipose tissue (WAT). Beige adipocytes share some characteristics with brown adipocytes such as the expression of UCP1. Beige adipocytes can be activated by environmental stimuli or pharmacological treatment, and this change is accompanied by an increase in energy consumption. This process is called white browning, and it facilitates the maintenance of a lean and healthy phenotype. Thus, promoting beige adipocyte development in WAT shows promise as a new strategy in treating obesity and related metabolic consequences. In this review, we summarized the current understanding of the regulators and hormones that participate in the development of brown fat and white fat browning.
Keywords: buněčná diferenciace; Adipose Tissue, White; hnědá tuková tkáň; bílá tuková tkáň; hormony; transkripční faktory; Animals; Humans; Gene Expression Regulation; lidé; Adipose Tissue, Brown; zvířata; regulace genové exprese; Transcription Factors; Cell Differentiation; Hormones